“Perfect Leader, Perfect Leadership?” Linking Leaders’ Perfectionism to Monitoring, Transformational, and Servant Leadership Behavior - Otto, Kathleen; Geibel, Hannah V.; Kleszewski, Emily (Frontiers in Psychology, 2021)
Despite the growing interest in perfectionism and its many facets, there is a lack of research on this phenomenon in the context of leadership. Attending to this deficit, the present study is the first to investigate the relationship between the three facets of perfectionism (self-oriented, socially prescribed, and other-oriented perfectionism) and three types of self-rated leadership behavior. In Study 1 (N = 182), leaders’ perfectionism and its association to their organizational, goal-oriented leadership behavior—self-rated as transactional (management by exception) and transformational leadership—is explored. In Study 2 (N = 185), the relationship of leaders’ perfectionism to their servant leadership as a people-centered leadership behavior is investigated. In line with the perfectionism social disconnection model (PSDM), we assume other-oriented and socially prescribed perfectionism to be positively related to management by exception (i.e., monitoring behavior) and negatively related to transformational and servant leadership, whereas the opposite pattern is primarily predicted for self-oriented perfectionism. Our findings in Study 1 reveal a negative relationship between leaders’ self-oriented perfectionism as well as positive relationships to their other-oriented and socially prescribed perfectionism in management by exception, while no substantial correlations with transformational leadership have emerged. In Study 2, a negative association between other-oriented perfectionism and the forgiveness dimension of servant leadership is revealed, indicating a possible barrier to building interpersonal relationships of acceptance and trust. Additionally, self-oriented perfectionism has been proven to be a rather favorable trait in servant leadership.